Searching and parasitism behaviour of Trichospilus pupivorus (Hymenoptera: Eulophidae), a potential parasitoid for coconut black-headed caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - Nor Ahya Mahadi,; Tajul Ariffin Aziz Yusof,; Rozeita Laboh, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
Black-headed caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) is one of the major pests of coconut in Asian countries including India, Sri Lanka, Bangladesh, Pakistan, Myanmar, China and Thailand. Recently, the pest has been detected in two (2) acres of aromatic (Pandan) coconut palms (Cocos nucifera) in Cherating, Pahang. Nearly 60% of coconut palms have been infested by the caterpillar and caused extensive defoliation of coconut leaves. For interim control measure, chemical pesticides have been applied for several times, however the infestations still exist. Therefore, an alternative effort to manage the pest by using biological control method has been initiated. As an initial experiment, a study on searching and parasitism behaviour of naturally occurred parasitoid namely as Trichospilus pupivorus (Hymenoptera: Eulophidae) has been conducted. In a no choice and choice experiment, three (3) types of host were prepared as follows: (i) unparasitized, (ii) parasitized and (iii) empty (control) host in ventilated glass vials which served as parasitism areas with ten hosts per category. Female parasitoids were then released into the areas and allowed to search for their host for two (2) hours. The experiments were done in complete randomised design (CRD) with five (5) replications each. Data on parasitoids behaviour, time duration for each behavioural stages and host preferences were recorded throughout the activity. Results showed that T. pupivorus significantly preferred the unparasitized host compared to the other treatments (P<0.05). Overall, there were six (6) stages of behaviour as they completed the parasitism process. The females spent most of their time parasitizing a host and successfully completed the entire parasitism phase in 98.12 minutes. Further observation should be carried out to ensure whether its parasitism ability would outweigh the long time-duration of parasitism process.